MapReduce with Components for Processing Big Graphs - de Rezende, Cenez Araújo; de Carvalho Junior, Francisco Heron (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2018)
BigGraph applications have been mostly implemented with largescale parallel processing frameworks based on MapReduce. However, it continues to be challenging to meet their particular requirements, even despite the emerging of alternative models, such as Pregel. This paper introduces a component-oriented design for graph processing frameworks, by using HPC Shelf, a component-based cloud computing platform for HPC services.